A discourse analysis of the collective memory constructed in the Fietas Public Art Project - Hu, Binjun (My University, 2014)
This research report is a selective examination of the impact of the Fietas mural project which commemorates the apartheid-era forced removals of residents from Fietas in Johannesburg on members of the affected community. It begins with a consideration of the concept of collective memory, alluding to some of the problems in relation to public art projects. Boym’s two types of nostalgia are the primary theories reflected in the project. A comparative analysis of commemoration and memory-work in a global context that include Germany, Denmark, Norway, China and Japan is articulated in an attempt to contextualize South African memorialisation within an international frame of reference. The report follows mostly Norman Fairclough’s discourse analysis method to interpret informant’s memories of Fietas with a particular interest in ideas about difference and assumptions, especially those which are extra-experiential. The findings of the discourse analysis demonstrates how the discourse of the collective memory of Fietas is built out of a complex interrelationship of the two objects: Fietas and the mural. The discussion of the results argues that the collective memory of Fietas constructed by the mural reflects the conspiracy of a single plot proposed by restorative nostalgia. However, this romanticized version of collective memory requires the function of reflective nostalgia, which opens up possibilities of multiple versions of collective memory of Fietas. Based on the discussion of the typology of nostalgia and associated arguments of collective memory, the report suggests two characteristics of collective memory which are respectively mobility and immobility. It then includes another voice in the discourse from the Play Urban project to validate the argument. Lastly, some recommendations in addressing the limitations of this research study are offered.